Resolving Pigging Stalls in Low-Pressure Offshore Gas Pipelines: A Case Study on Pressure Optimization at Offshore Southeast Sumatra, Indonesia - Nauval Rizki Muhammad; Meidiya Putra Riko; Rasyid Ridho Muhammad; Chandra Kosasi Daviq; Fadly Enriko; Anang Safii Erik; Mujiburochman Muhamad (E3S Web of Conferences)
A pigging stall occurred in a 5.9 km, 16-inch offshore gas pipeline, connecting an offshore platform to a Floating Storage Offloading Unit (FSO), due to insufficient platform pressure (~60 psig). The stalled pigging operation halted production and created significant operational inefficiencies. The aim of this study was to determine the minimum pressure required to prevent further pig stalls. A detailed flow assurance analysis, using multiphase transient modeling, identified that the optimal launching pressure to ensure pigging continuity was between 78-80 psig. Following these recommendations, field trials were conducted, successfully eliminating the stall and restoring pipeline functionality. These findings underscore the critical role of pressure optimization in pigging operations and highlight the effectiveness of flow assurance methodologies in mitigating operational risks and ensuring uninterrupted production.